Evaluasi Kinerja Lalu Lintas pada Simpang Bersinyal Marvel Menggunakan Metode MKJI 1997 dan Simulasi VISSIM - Hariza, Sakhwal; Hartatik, Nurani (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
The traffic performance evaluation at Marvel Intersection in Surabaya was conducted using two main approaches: the Indonesian Highway Capacity Manual (MKJI) 1997 and micro-simulation with PTV VISSIM software. This study aims to analyze the intersection’s performance based on parameters such as degree of saturation (DS), average delay, queue length, and level of service (LOS). Primary data were collected through traffic volume surveys and geometric observations, while secondary data were obtained from relevant agencies. The results indicate that the Marvel Intersection experiences significant congestion during peak hours, with LOS approaching category F. Model validation was performed by comparing VISSIM simulation results with MKJI 1997 calculations to ensure accuracy. The validation process showed acceptable error levels, confirming the reliability of both methods. Based on the findings, improvement proposals such as signal cycle time optimization and re-evaluation of traffic flow distribution are suggested to enhance intersection performance. This research also emphasizes the importance of integrating manual and simulation-based approaches in urban traffic performance analysis. The use of both methods provides a comprehensive.